2002
DOI: 10.1258/0956462021924884
|View full text |Cite
|
Sign up to set email alerts
|

HIV treatments optimism is associated with unprotected anal intercourse with regular and with casual partners among Australian gay and homosexually active men

Abstract: We examined HIV optimism and unprotected anal intercourse (UAI) in a nationwide sample of gay and homosexually active men. Questionnaires were distributed throughout Australia through pornographic catalogues. 1832 men responded, 1181 (64.5%) classified as gay community attached (GCA) and 651 (35.5%) as non-GCA (NGCA). Mean HIV optimism scores tended toward scepticism rather than optimism, with no significant difference between GCA and NGCA men. Men who had UAI with regular partners were significantly more opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 2 publications
4
23
2
2
Order By: Relevance
“…This has coincided with changes in the external forces that drove gay men together in previous decades. Gay men have largely achieved legal equality, and homophobia in society has weakened; simultaneously, effective HIV treatments have made HIV a much lesser threat to gay men's lives than it once posed [17,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…This has coincided with changes in the external forces that drove gay men together in previous decades. Gay men have largely achieved legal equality, and homophobia in society has weakened; simultaneously, effective HIV treatments have made HIV a much lesser threat to gay men's lives than it once posed [17,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…HIV-negative MSM (Kelly et al, 1998;Remien et al, 1998;Kalichman et al, 1998;Vanable et al, 2000;Huebner & Gerend, 2001;Ostrow et al, 2002;Elford et al, 2002;Van de Ven, Rawstorne, Nakamura, Crawford, & Kippax, 2002;International Collaboration on HIV Optimism, 2003;Stolte & Dukers, 2003;Williamson & Hart, 2004;Huebner et al, 2004;Stolte et al, 2004;Halkitis et al, 2004). One previous study among young MSM in the United States (Koblin et al, 2003), and work in Australia (Van de Ven, Prestage, French, Knox, & Kippax, 1998) did not find such an association.…”
Section: Discussionmentioning
confidence: 99%
“…Optimistic beliefs based on the availability of HAART have been associated with high risk sex behaviors in many studies (Kelly, Hoffman, Rompa, & Gray, 1998;Remien, Wagner, Carballo-Dieguez, & Dolezal, 1998;Kalichman, Nachimson, Cherry, & Williams, 1998;Vanable, Ostrow, McKirnan, Taywaditep, & Hope, 2000;Huebner & Gerend, 2001;Ostrow et al, 2002;Elford et al, 2002;Van de Ven et al, 2002;International Collaboration on HIV Optimism, 2003;Williamson & Hart, 2004;Huebner, Rebchook, & Kegeles, 2004;Stolte, Dukers, Geskus, Coutinho, & de Wit, 2004), and these associations have reported to be significant in a recent meta-analysis (Crepaz, Hart, & Marks, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…International research assessing the characteristics of HIV-positive people has largely focused on sexual behaviour, particularly unprotected sex that may result in the onward transmission of HIV (Aidala, Lee, Garbers, & Chiasson, 2006;Elford, 2006;Ostrow, McKirnan, Klein, & DiFranceisco, 1999;Scheer et al, 2008;van Kesteren, Hospers, & Kok, 2007). Reviews suggest that rates of unprotected sex reported by HIV-positive (and HIVnegative) gay men have increased since ART became available in many countries, including Australia (Elford, 2006;van Kesteren et al, 2007).…”
Section: Introductionmentioning
confidence: 99%